Single Mode Photonic Crystal Vertical Cavity Surface Emitting Lasers. (14th February 2012) - Choquette, Kent D.; Siriani, Dominic F.; Kasten, Ansas M.; Tan, Meng Peun; Sulkin, Joshua D.; Leisher, Paul O.; Raftery, James J.; Danner, Aaron J.
Abstract : We review the design, fabrication, and performance of photonic crystal vertical cavity surface emitting lasers (VCSELs). Using a periodic pattern of etched holes in the top facet of the VCSEL, the optical cavity can be designed to support the fundamental mode only. The electrical confinement is independently defined by proton implantation or oxide confinement. By control of the refractive index and loss created by the photonic crystal, operation in the Gaussian mode can be insured, independent of the lasing wavelength.